2018
DOI: 10.1152/ajpregu.00430.2017
|View full text |Cite
|
Sign up to set email alerts
|

Role of respiration in the cardiovascular response to orthostatic and mental stress

Abstract: The objective of this study was to determine the response of heart rate and blood pressure variability (respiratory sinus arrhythmia, baroreflex sensitivity) to orthostatic and mental stress, focusing on causality and the mediating effect of respiration. Seventy-seven healthy young volunteers (46 women, 31 men) aged 18.4 ± 2.7 yr underwent an experimental protocol comprising supine rest, 45° head-up tilt, recovery, and a mental arithmetic task. Heart rate variability and blood pressure variability were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 39 publications
2
16
0
2
Order By: Relevance
“…In order to verify the reproducibility of an autonomic pattern characteristic for supin, stand, supin01, and stand01 we calculated the following linear parameters: absolute values, changes of mean, and standard deviation of RRI. The absolute values and their changes were in accordance with the literature (Javorka et al, 2018;Valente et al, 2018), where supin was characterized by slight parasympathetic dominance (Levy and Martin, 1996), stand by sympathetic dominance ( Table 1, decrease of mean RRI and SD with respect to supin, Table 2, Sobiech et al, 2017), supin01 with maximized parasympathetic dominance (Table 1, increase of SD with respect to supine, Shields, 2009) and stand01 with combined situation of higher sympathetic tone on mean RRI regulation (decrease of mRRI with respect to supin01, Table 1) with variability, most probably parasympathetically mediated, comparable to the supin values ( Table 1, supin-stand01, Table 2, p = 0.831).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In order to verify the reproducibility of an autonomic pattern characteristic for supin, stand, supin01, and stand01 we calculated the following linear parameters: absolute values, changes of mean, and standard deviation of RRI. The absolute values and their changes were in accordance with the literature (Javorka et al, 2018;Valente et al, 2018), where supin was characterized by slight parasympathetic dominance (Levy and Martin, 1996), stand by sympathetic dominance ( Table 1, decrease of mean RRI and SD with respect to supin, Table 2, Sobiech et al, 2017), supin01 with maximized parasympathetic dominance (Table 1, increase of SD with respect to supine, Shields, 2009) and stand01 with combined situation of higher sympathetic tone on mean RRI regulation (decrease of mRRI with respect to supin01, Table 1) with variability, most probably parasympathetically mediated, comparable to the supin values ( Table 1, supin-stand01, Table 2, p = 0.831).…”
Section: Discussionsupporting
confidence: 90%
“…Also, the research on the orthostasis effect on HRV has been well-documented (De Souza et al, 2014;Zaidi and Collins, 2016;Valente et al, 2018) and is routinely used as a sensitive test for the evaluation of "physiological adaptive mechanisms" generated by the autonomic nervous system (head up tilt, Zygmunt and Stanczyk, 2010;Hoshi et al, 2019). Most of the studies that evaluate HRV in these physiological conditions (supine position, standing, supine position with 0.1 Hz breathing and standing with 0.1 Hz) focused on linear properties of HRV (Kabir et al, 2011;de Paula Vidigal et al, 2016;Javorka et al, 2018;Jha et al, 2018). However, non-linear properties quantify and explain up to 80% of total RRI variability (Vandeput, 2010) and reflect physiological mechanisms of multiinteracting cardiovascular control, mostly exerted through sympatho-vagal effectors operating in nonlinear fashion (de Godoy, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During cognitive load, parasympathetic withdrawal and sympathetic activation are presumably initiated by projections from the amygdala and occur without major changes in venous return. Thus, mental stress is accompanied by a decrease of parasympathetic activity and/or an increase of the sympathetic activity (Kuipers et al 2008, Widjaja et al 2015; in this condition, RSA magnitude is usually decreased (Allen and Crowell 1989, Bernardi et al 2000, Herbert et al 2010, Wetzel et al 2006, Javorka et al 2018. In addition to these previous findings, we observed that the information flow from RESP to RR was amplified as regards the indirect connection during MA, but the degree of indirectionality was significantly lower than that during HUT (P=0.0255) (Fig.…”
Section: Discussionmentioning
confidence: 99%